Early Jewish prayers in Greek - Horst, Pieter Willem van der (Commentaries on early Jewish literature., 2008)
"In this volume a series of 12 Jewish prayers, composed by Greek speaking communities, have been collected, translated, and provided with an extensive historical and philological commentary. These prayers, ranging in time from the second century BCE to the fourth century CE, offer unique insights into a wide variety of forms of Jewish spirituality, both in the land of Israel and in the Diaspora. They have been preserved on papyrus, on stone, and as part of Christian church orders into which some of them have been incorporated."--Jacket.